Website and E-Marketing for AL-SULTAN FURNITURE - SHAHD SAIF; ROAA ALSHAIKH (My University, 2024)
This project focuses on developing a website and e-marketing strategy for Al-Sultan Furniture, a company that started in 2010 specializing in sofa upholstery and has since expanded to offer a wide range of household furniture and customization services. The project aims to address several challenges faced by the business, such as declining sales due to external factors, limited social media engagement, and inadequate product display and data analysis. The proposed solutions include creating a WordPress-based website, improving data collection and analysis, and enhancing social media marketing through targeted campaigns on Facebook and Instagram. The project also outlines a comprehensive e-marketplace model and social media strategy, including segmentation, targeting, positioning, and the use of various analytics tools to measure effectiveness. Additionally, the project sets specific objectives for increasing online sales, customer satisfaction, social media engagement, and operational efficiency through the use of advanced analytics and automated marketing techniques. The implementation of these strategies is expected to boost Al-Sultan Furniture's market presence and customer base by leveraging digital platforms and enhancing the overall shopping experience.